Biology and Management of Johnsongrass (Sorghum halepense) in Ornamental Crop Production and Landscapes - Ping Yu; Ernest Kraka; Chris Marble (EDIS)
Johnsongrass is a warm-season perennial grass and one of the most persistent and troublesome weeds in the southern United States. This new 5-page publication of the UF/IFAS Environmental Horticulture Department was developed to help commercial nursery growers, landscapers, and other green industry professionals identify and manage johnsongrass. Written by Ping Yu, Ernest Kraka, and Chris Marble. https://edis.ifas.ufl.edu/ep620